African cultures and the challenges of quality education for sustainable development (2018)
In 2015, the world, through UNESCO adopted the 2030 agenda for sustainable development floated on 17 Sustainable Development Goals (SDGs) to “transform our world.” SDG4 titled Quality Education seeks to “ensure inclusive and equitable quality education for all and promote lifelong learning.” An ordinary look at SDG4 would make it appear as an extension of Education for All. However, there are differences. One difference that stands out is the undercurrent of the need to connect education to the key indicators of existence in its context especially through learning and equity. SDG4, as indeed many policies and agenda at the global level, tends to face challenges peculiar to the uniqueness of the African continent. Most governments struggle to include such goals in their national plans in ways that connect the real context of their people. One major area of concern for us is the area of culture where most programmes introduced into Africa, including into schools, are dressed in cultures foreign to the receiving communities. The authors of this paper argue that for SDG4 and similar programmes to fulfill their objective; they must find ways of embracing and adapting authentic African culture. The authors theorise in literature and use African cultures to drive its analysis. We conclude that African culture is the most viable framework for ensuring quality education that causes and sustains development along the lines envisaged by SDG4.